2023
DOI: 10.1097/ijg.0000000000002256
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Telephone-Based Outreach Reconnects Glaucoma Patients With Subspecialty Care

Abstract: Précis: A personalized telephone-based intervention is a costeffective method to return overdue patients with open angle glaucoma (OAG) to subspecialty care. Patients who accepted care overwhelmingly preferred in-person appointments with their provider instead of hybrid visits with telehealth.Purpose: To evaluate the effectiveness of a telephone-based outreach strategy to reconnect OAG patients with subspeciality care.Patients and Methods: Established patients with OAG who were seen before March 1, 2021, but h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…34 This limitation was addressed by conducting a detailed chart review to enhance the accuracy of the clinical classification of each patient identified for outreach. [23][24][25] Despite finding a strong association between age and becoming LTFU, none of the other characteristics investigated here predicted which patients were more likely to be reached or accept a return to eye care when contacted. The definition of LTFU used in this study may also have inadvertently selected patients who faced more serious or insurmountable barriers to returning for care.…”
Section: Limitationsmentioning
confidence: 58%
See 2 more Smart Citations
“…34 This limitation was addressed by conducting a detailed chart review to enhance the accuracy of the clinical classification of each patient identified for outreach. [23][24][25] Despite finding a strong association between age and becoming LTFU, none of the other characteristics investigated here predicted which patients were more likely to be reached or accept a return to eye care when contacted. The definition of LTFU used in this study may also have inadvertently selected patients who faced more serious or insurmountable barriers to returning for care.…”
Section: Limitationsmentioning
confidence: 58%
“…Previous telehealth studies targeting patients with open-angle glaucoma or diabetic retinopathy achieved higher success rates in returning patients to eye care. [22][23][24][25] This may be attributed, in part, to the younger age of patients with those conditions compared to advanced AMD. While the goal was to achieve a higher return rate for in-person eye care, contacting patients, including through a family member or healthcare proxy, fulfils the obligation to provide continued care.…”
Section: Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation